Self Efficacy of Elderly Congregation in Building Learning Motivation (Study at Alif Lam Mim Kajen Islamic Boarding School) - Rifani Raniasati; Aris Priyanto; Maaz Ud In (Prosperity: Journal of Society and Empowerment, 2022)
Someone who ages without mental preparation often experiences a decrease in quality of life. At an advanced stage, there are many psychosocial crises experienced by the elderly. The feeling of basic trust that develops in the elderly is more dominated by dystonic or “desperate” traits. Not all elderly people have efficacy or beliefs about good self-acceptance of deficiencies and changes that occur to them. The purpose of this research is to photograph a different reality, namely how the elderly are able to maintain their learning motivation through strengthening self-efficacy and what factors influence the level of self-efficacy of the elderly congregation. The method used in this research is qualitative method. This research is a field research with descriptive-analytic analysis. Based on data and analysis in the field, the results showed that the elderly congregation at the Alif Lam Mim Islamic Boarding School, had good self-efficacy. This can be seen from the enthusiasm and effort they put in even in the midst of deficiencies and disturbances both physically and psychologically. Self-efficacy in the elderly is influenced by things such as past experiences, modeling, self-esteem, and emotional states. This research is expected to be a review, consideration and support for community development and development strategies, especially in empowering the elderly.